KECUKUPAN ASUPAN PROTEIN DAN ASUPAN VITAMIN B12 PADA ANAK VEGETARIAN DI SEKOLAH DASAR METTA MAITREYA - Rafika Rahmi; Tuti Restuastuti; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTVegetarian is a lifestyle that does not consume meat, poultry, or fish and derivedproducts. The only vegetarian foods derived from plants except the lacto vegetarian, ovovegetarians and lacto-ovo vegetarians who still eat eggs, milk and other dairy products. In thefuture age children during growth and development of nutritional intake is essential, not onlyto sustain life but to the process of growth and development. occur concern for body weightand body shape. Protein and vitamin B12 important moment in the growth and growingchildren. Protein and vitamin B12 deficiency will cause vitamin B12 deficiency can interferewith the growth in children and nervous system resulting in symptoms of ignorance, anemia,irritability, or offended. This descriptive study aimed to describe the adequate intake ofprotein and vitamin B12 in vegetarian children in elementary school (SD) Metta Maitreya.The sample used in this study is total sampling. Adequate intake of protein and vitamin B12was assessed by using the FFQ (Food Frequency Questionnaire). Of the 34 samples found thenumber of women (55%) more in comparison to men (45%), age group 7-9 years were themost (56%), while those undergoing Lacto-ovo vegetarian diet as much (68%) and vegetarianin the womb as much as 67%, while the protein intake of 100% is said to intake more. Forintake of vitamin B12 intake 75% mentioned experiencing vitamin B12 lessKeywords: vegetarian, protein, vitamin B12